2013
DOI: 10.1167/iovs.12-10904
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-204-5p Regulates Epithelial-to-Mesenchymal Transition during Human Posterior Capsule Opacification by Targeting SMAD4

Abstract: Our data provide firm evidence of a role for miR-204-5p in the direct regulation of EMT through its targeting of SMAD4 and, consequently, TGF-β signaling. Because of its ability to repress the EMT, miR-204-5p may be a novel target for PCO therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…In contrast to the above results, the mRNA levels of miR204, miR184, TGFβR2, TGFβR3, and BMP4, which have been previously shown to be downregulated by TGFβ2 in HLE cells (Dawes et al ., 2007; Wang et al ., 2013), were expectedly downregulated by the TGFβ2 treatment (Fig. 4).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast to the above results, the mRNA levels of miR204, miR184, TGFβR2, TGFβR3, and BMP4, which have been previously shown to be downregulated by TGFβ2 in HLE cells (Dawes et al ., 2007; Wang et al ., 2013), were expectedly downregulated by the TGFβ2 treatment (Fig. 4).…”
Section: Resultsmentioning
confidence: 85%
“…Numerous studies have implicated the TGFβ/Smad signaling pathway in PCO (Saika et al ., 2004; Wormstone et al ., 2004). αSMA, MMP2, CTGF, integrin αV, integrin α5, integrin β1, miR4279, and miR1469 have been shown to be upregulated by TGFβ2 during the EMT of HLE cells (Dawes et al ., 2007; Wang et al ., 2013; Mamuya et al ., 2014). Therefore, we measured the mRNA levels of these proteins by qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, another study in our lab found that the expression of miR-204-5p was downregulated 66.8-fold in human posterior capsule opacification (PCO) tissues compared to those in the normal attached lens epithelial cells (LECs). 15 These data uncovered the multiexpression pattern of miR-204-5p in the eye, suggesting miR-204-5p may be one of the key miRNAs in different diseases of the eye. We then investigated the role of miR-204-5p in regulating SIRT1 in diabetic keratopathy.…”
mentioning
confidence: 82%
“…By targeting SMAD4 , miR-204-5p inhibits EMT in the LECs of a human donor capsular bag model in vitro. Development of PCO involves miR-204-5p and SMAD4 in the EMT, and hence miR-204-5p serves as a novel target for therapeutic intervention in PCO [25]. In addition to miR-204-5p, miR-26b was also found to target SMAD4 mRNA.…”
Section: Mirnas and Eye Disordersmentioning
confidence: 99%